Tantangan Pandemik Dalam Mempengaruhi Kontribusi Kompetensi Terhadap Kinerja Pegawai: Studi Kasus Pada Bagian Umum Pemda, Kabupaten Dompu - Putri, Dwi Rahmi (Journal of Sharia Economy and Islamic Tourism, 2024)
This study aims to determine the Pandemic Challenges In Influencing Competence Contributions to Employee Performance: A Case Study in the General Section of the Regional Government, Dompu Regency. The sample in this study were all 78 employees of the Dompu Regency Regional Government Office. The data collection technique uses a questionnaire with a power collection tool using a questionnaire that has been tested for validity and reliability. The results of this study indicate that Pandemic Challenges Can Affect the Contribution of Competence to Employee Performance: A Case Study in the General Section of Local Government, Dompu Regency.